The role of herbal medicine in mental health care among VaTsonga traditional healers - Mashele, Lindeni Glacious (My University, 2023)
Mental disorders are fast becoming a global health concern, with one in eight people living with some form of mental illness. People respond to mental illness in a variety of ways, including the use of professional, religious, and/or traditional interventions. This study explored herbal medicinal products used by Tsonga traditional healers and their psychopharmacological benefits in mental health care. The study has been guided by the qualitative phenomenological research design. A total of seven traditional healers (female = 86%; between 35–88 years of age) were purposively sampled and qualitatively interviewed. The collected data were analysed using Interpretative Phenomenological Analysis (IPA). Several plant species and herbal concoctions were identified as some of the medicinal products used to treat diverse mental health conditions. Some herbs are prescribed therapeutically as sedatives while others are prescribed for the treatment of stress, depression, psychosis, and substance abuse. The findings further reveal that herbal medicinal products are reported to be effective, non-toxic, and without adverse side effects. In conclusion, the study recommends that professionals and traditional healers collaborate in mental health-care research and practice. Collaboration between the two stakeholders could also improve mental health care by enriching training in each field. .
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2023
Keywords: Traditional medicines; Traditional herbs; Traditional healers; Mental illness; Indigenous knowledge systems; Medicinal plants; Healers -- Africa; Herbs -- Therapeutic use; Mental health; Alternative medicine